Dampak Penyalahgunaan Mobil Dinas oleh Oknum ASN dari Perspektif Etika Birokrasi Darwin 1999 - septi - wulandari; Nyiratih Haruming Ayu Hapsari (JURNAL SOSIAL Jurnal Penelitian Ilmu-Ilmu Sosial, 2022)
Abstract— This paper describes the impact of misuse of official cars by ASN in the perspective of Darwin 1999 bureaucratic ethics. The research method used in this research is descriptive qualitative, while the approach used is Darwin 1999 bureaucratic ethics theory approach. Darwin 1999 means that bureaucratic ethics is a all forms of the function of bureaucratic ethics, namely acting as a guide for public administration in carrying out their duties and authorities so that actions in the bureaucracy as a standard for assessing whether the nature, behavior, and actions of the public bureaucracy are considered good, bad, blameworthy, and commendable. Ethical violations committed by ASN elements, in the form of abuse of authority related to official cars, have their own impact on ASN and create a negative image of ASN. The use of official cars for personal purposes is an ethical and legal violation. The author uses the theory of bureaucratic ethics to see government control in dealing with unscrupulous ASN actors for non-ethical behavior. One form of government control in regulating ASN disciplinary actions is regulated in PP No. 53 of 2010. Keywords : Abuse; Official Car; Bureaucratic Ethical Theory